PENEGAKAN HUKUM TERHADAP KEKERASAN SEKSUAL TERHADAP ANAK MENURUT UNDANG-UNDANG NO.35 TAHUN 2014 (STUDI KASUS POLRES BANGKALAN) - Chandra Anggara Putra; Haniyah (INTELIGENSIA MEDIA, 2024)
Sexual violence against children is a serious problem that requires effective legal treatment. This study aims to analyze law enforcement against sexual violence against children based on Law No. 35 of 2014 in the jurisdiction of Bangkalan Police Station This study uses a type of empirical legal approach. Data is obtained by examination of case files, and analysis of related documents. The results showed that the Bangkalan Regional Police has made maximum efforts in law enforcement against sexual violence against children. Factors such as lack of public awareness, limited resources, and legal constraints are still challenges in handling this case. However, there have been improvements in coordination between law enforcement agencies, strengthening aspects of child protection, and adoption of technology in investigations. The conclusion of this study is the need for increased cooperation between authorities, communities, and child protection agencies to ensure more effective law enforcement. Prevention and education efforts need to be increased to address the root causes of sexual violence against children. The implications of these findings can be used as a basis for relevant parties in designing more effective and sustainable policies to protect children from sexual violence